Circulating Tumor DNA: A Biomarker for Adjuvant Treatment Response in Stage III Colon Cancer - Sallam, Yasser Ahmed; Fouad El Deftar, Mervat Mohamed; Abouelkasem, Fatma Mohamed Ahmed; Nada, Yousery; Seleam, Mohammed Samy (Journal of Neonatal Surgery, 2025)
In this prospective work, our purpose was to evaluate the impact of circulating tumor DNA (ctDNA) analyses before, during and after adjuvant chemotherapy in completely resected stage III colon cancer patients, particularly in terms of disease-free survival (DFS). Additionally, we aimed to estimate the efficacy of adjuvant chemotherapy in decreasing ctDNA levels in the plasma. From January 2023 to December 2023, 77 patients with stage III colon cancer underwent complete surgical resection, were included in this study. These patients had undergone upfront resection of their primary tumors. All received adjuvant chemotherapy (CAPEOX or FOLFOX regimen) for six-month period. The median followup was 21 months from date of primary surgery. After six months of treatment, ctDNA levels were significantly associated with two-year DFS. Patients with low ctDNA levels exhibited better DFS compared to those with moderate ctDNA levels, who in turn had better DFS than patients with high-level ctDNA. Findings confirm the benefit of adjuvant chemotherapy in eradicating residual tumor cells responsible for tumor recurrence or metastasis.